Time and Concentration Dependent Effects of Short Chain Fatty Acids on Lipopolysaccharide- or Tumor Necrosis Factor α-Induced Endothelial Activation - Li, Meng; van Esch, Betty C. A. M.; Henricks, Paul A. J.; Garssen, Johan; Folkerts, Gert (Frontiers in Pharmacology, 2018)
Background and Aim: Endothelial activation is characterized by excessive production of cytokines and chemokines as well as adhesion molecules expression which is involved in the development of atherosclerosis. The aim of our study is to investigate the effects of short chain fatty acids (SCFA) on lipopolysaccharide (LPS) or tumor necrosis factor alpha (TNFα)-induced endothelial activation. Methods and results: Human umbilical vein endothelial cells (HUVEC) were pre-treated with acetate (10mM), butyrate (0.1mM) or propionate (0.3mM) for 1h, 16h or 24h and then stimulated with LPS (1µg/ml or 10µg/ml) or TNFα (100pg/ml or 1ng/ml) for 6h, 12h or 24h. Cytokines in the supernatant were measured by ELISA. HUVEC were pre-treated with acetate (10mM), butyrate (5mM) or propionate (10mM) for 24h and then stimulated with LPS (1ug/ml) or TNFα (1ng/ml) for 8h. The expression of the adhesion molecules intracellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) was detected by flow cytometry. The human blood mononuclear cell adhesive level to HUVEC monolayer was measured. LPS and TNFα induced a significant increase in the release of interleukin-6 (IL-6) and IL-8. Acetate, butyrate and propionate reduced IL-6 and IL-8 levels and the magnitude was dependent on the incubation times. LPS or TNFα increased ICAM-1 and VCAM-1 expression. Pre-incubation with acetate had no effect. In contrast, butyrate and propionate decreased VCAM-1 expression in TNFα stimulated cells but showed no effects on ICAM-1 expression. Butyrate significantly inhibited the adhesion of mononuclear cells to an endothelial monolayer and propionate was less effective. Conclusion: SCFA, including acetate, butyrate and propionate, influenced LPS- or TNFα-induced endothelial activation by inhibiting the production of IL-6 and IL-8, and reducing the expression of VCAM-1and subsequent cell adhesion. Results were dependent on the concentrations and pre-incubation time of each SCFA and stimulation time of LPS or TNFα.